The Effect of Reminiscence Therapy on the Assessment of Depression, Anxiety and Self-Esteem in Community-Dwelling Older Adults: An Intervention Study - Zeleníková, Renáta; Hosáková, Jiřina; Kozáková, Radka; Bobčíková, Katka; Bužgová, Radka (International journal of older people nursing, 2025)
BACKGROUND: Reminiscence therapy (RT) is a widely used approach to promote well-being among older adults and is an effective intervention method for older adults with diverse health conditions, including community-dwelling older adults. OBJECTIVES: The aim of the study was to determine the impact of group RT on assessments of depression, anxiety and self-esteem in older adults living in the community. METHODS: We implemented sessions of group simple RT. The sample consisted of 24 older adults living in the community who attended a 12-week RT course. The duration of each reminiscence session was 60 min. The average age of the sample was 74.7 years. We used the Geriatric Depression Scale, the Geriatric Anxiety Inventory, the Rosenberg self-esteem scale, the Older adults' Quality of Life-Brief version and the Sense of Coherence scale to assess mental health outcomes before and after intervention. RESULTS: After intervention, we observed statistically significant improvements in assessments of depression (p < 0.001), anxiety (p = 0.011), self-esteem (p = 0.007) and the comprehensibility dimension of the sense of coherence scale (p = 0.039). Depression showed the largest effect size (Cohen's d = 0.870; 95% CI: 0.392 to 1.335), indicating a large effect, followed by self-esteem (Cohen's d = 0.612; 95% CI: -1.044 to -0.170) and anxiety (Cohen's d = 0.543; 95% CI: 0.108 to 0.967), both of which demonstrated a moderate effect. CONCLUSIONS: We found group RT to be effective for several outcomes among older adults. Reminiscence is a good non-invasive treatment for the promotion of mental health in community-dwelling older adults. IMPLICATIONS FOR PRACTICE: As research has now established RT to be an essential component of activities for older adults in senior care facilities, we should also offer it to those living in the community as an effective activity for the promotion of healthy aging among older adults.
Keywords: lidé; Anxiety; Independent Living; Female; deprese; Quality of Life; Humans; Self Concept; Geriatric Assessment; úzkost; samostatný způsob života; mužské pohlaví; sebepojetí; Psychotherapy, Group; Depression; ženské pohlaví; geriatrické hodnocení; Aged, 80 and over; senioři nad 80 let; kvalita života; Aged; Male; skupinová psychoterapie; senioři